Effect of Low- and High-Glycemic Load on Circulating Incretins in a Randomized Clinical Trial - Runchey, Shauna S. (2012)
OBJECTIVE: Low-glycemic load diets lower post-prandial glucose and insulin responses; however, the effect of glycemic load on circulating incretin concentrations is unclear. We aimed assess effects of dietary glycemic load on fasting and post-prandial glucose, insulin and incretin (i.e., glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1)) concentrations and to examine for effect modification by adiposity. MATERIALS AND METHODS: We conducted a single-center, randomized controlled crossover feeding trial in which a subset of participants had post-prandial testing. Participants were recruited from the local Seattle area. We enrolled 89 overweight-obese (BMI 28.0–39.9 kg/m(2)) and lean (BMI 18.5–25.0 kg/m(2)) healthy adults. Participants consumed two 28-day, weight-maintaining high- and low-glycemic load controlled diets in random order. Primary outcome measures were post-prandial circulating concentrations of glucose, insulin, GIP and GLP-1, following a test breakfast. RESULTS: Of the 80 participants completing both diet interventions, 16 had incretin testing and comprise the group for analyses. Following each 28-day high- and low-glycemic load diet, mean fasting concentrations of insulin, glucose, GIP and GLP-1 were not significantly different. Mean integrated post-prandial concentrations of glucose, insulin and GIP were higher (1504±476 mg/dL/min, p<0.01; 2012±644 µU/mL/min, p<0.01 and 15517±4062 pg/ml/min, p<0.01, respectively) and GLP-1 was lower (−81.6±38.5 pmol/L/min, p<0.03) following the high-glycemic load breakfast as compared to the low-glycemic load breakfast. Body fat did not significantly modify the effect of glycemic load on metabolic outcomes. CONCLUSIONS: High-glycemic load diets in weight-maintained healthy individuals leads to higher post-prandial GIP and lower post-prandial GLP-1 concentrations. Future studies evaluating dietary glycemic load manipulation of incretin effects would be helpful for establishing diabetes nutrition guidelines.